The writing program administrator's resource : a guide to reflective institutional practice - Brown, Stuart C. (Stuart Cameron), 1955-; Enos, Theresa; Chaput, Catherine (Lawrence Erlbaum Associates, 2002)
This is a collection of articles that addresses fundamental practices and issues encountered by writing programme administrators in their workplace settings. It offers a combination of theory and specific information on a range of topics that can be translated into institutional scholarship.